Performance of Putative Mutants and Genetic Parameters of Plectranthus amboinicus (L.) through Mutation Induction With Colchicine - Kunto Wibisono; Syarifah Iis Aisyah; Waras Nurcholis; Sri Suhesti (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Genetic enhancement in vegetatively propagated crops can be done through mutation induction. Colchicine-induced mutation is one of the methods that can be employed to increase plant genetic diversity. This study aimed to determine the effect of colchicine on the performance and genetic parameters of MV3 generation of Plectranthus amboinicus (L.). This study was conducted at the Laboratory of Agricultural Seed Management, Plantation Research and Development Center, from June 2018 to June 2019. Nodes and shoots were used as explants. Mutation induction was performed using colchicine at concentrations of 0%, 0.02%, 0.04%, and 0.06%. Explant regeneration and subculture were done on MS0 medium. The number of plantlets yielded were 59 (0% concentration of colchicine), 60 (0.02%), 81 (0.04%), and 80 plantlets (0.06%), respectively. Results indicated that colchicine-induced mutation in an in vitro culture was able to generate high genetic diversity in both quantitative and qualitative characters of the plantlets. At the concentration of 0.04%, colchicine produced the highest frequency of putative mutants (28.4%). Genetic parameters in MV3 generation of P. amboinicus plantlets showed that five quantitative characters, i.e. plantlet height, number of leaves, number of shoots, leaf length, and number of roots had high heritability values at a concentration around the LC50 value (0.0275%).